Bentuk Penyajiantari Silek Harimau Di Nagari Padang Laweh Kecamatan Koto VII Kabupaten Sijunjung - Suci Wahyuni Sukhma; Herlinda Mansyur (SENDRATASIK UNP, 2021)
The research aims to reveal, describe, and analyze the presentation form of Silek Harimau Dance in Padang Laweh village, Koto Tujuah District, Sijunjung Regency. This research belongs to a qualitative research using descriptive analysis method. The object of this research was Silek Harimau Dance in Padang Laweh village. The main instrument in this research was the researcher itself supporting by tools in the form of stationeries and a camera. The data were collected through literature study, observation, interview, and documentation. The steps of analyzing data were collecting the data, describing the data, and concluding the data. The results prove that the form of Silek Harimau Dance is presented in two groups in opposite directions. The elements of the presentation form consist of: (1) Motion. Silek Harimau dance consists of gripping and wrestling. (2) Floor design. It uses a straight line pattern. (3) Dancers. It is performed by 2 women and 3 men. (4) Music. It consists of gandang, tambur, oguang / gong and talempong. (5) Costumes. Female players of Silek Harimau dance wear purple or black clothes while the men wear tiger costumes. (7) Place and time of performance. It is performed at official events or festivals. Silek Harimau dance is a traditional dance of the community in Padang Laweh village, Koto VII District, Sijunjung Regency.